Should the Tigers be Protected?: A Survey on Opinions of Local Inhabitants of Bandhavgarh and Related Social Factors in the Conservation of Tigers - Partha Pratim Dube (Indonesian Journal of Social and Environmental Issues (IJSEI), 2022)
Increased human populations and the resulting encroachment of related anthropogenic land uses into natural landscapes which once afforded wildlife habitats is a global conservation concern. Of particular concern, are the human-wildlife conflicts perpetuated because of human populations’ growth in the area where large carnivores occur? These increasing conflicts may further impact the conservation of carnivores because of public concerns for human health and safety and economic impacts on subsistence agriculture. In India, increased population growth has impacted the natural habitats for the Bengal tiger (Panthera tigris tigris) and the related conflicts have impacted efforts to conserve the species. To better describe the social factors that may affect large carnivore conservation in India, we surveyed the tiger-affected people, the relatives of the people killed by tigers, and the common villagers in the adjacent villages of Bandhavgarh National Park of Madhya Pradesh in India. All of our questionnaires are related to the protection of tigers and the reasons behind it. This study featured the first assessment and basic data for understanding Bengal tigers in the area of Bandhavgarh Forest.